The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/8176898
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Pharmacologic Prophylaxis against Deep Vein Thrombosis in Medical Wards of an Ethiopian Referral Hospital

Abstract: Background Most of hospitalized patents are at risk of developing deep vein thrombosis (DVT). The use of pharmacological prophylaxis significantly reduces the incidence of thromboembolic events in high risk patients. The aim of this study was to assess appropriateness of DVT prophylaxis in hospitalized medical patients in an Ethiopian referral hospital. Methods Cross-sectional study design was employed. Patients with a diagnosis of DVT, taking anticoagulant therapy, and those who refused to participate were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In line with other studies reported from Ethiopia, 23 , 24 in the present study, the most common risk factors for VTE were acute infection/and rheumatologic disorder (76.7%), reduced mobility (41.1%), having heart and /or respiratory failure (21.5%), elderly age ⩾70 years (13.7%), active cancer (10.5%), and acute myocardial infarction or ischemic stroke (12.8%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with other studies reported from Ethiopia, 23 , 24 in the present study, the most common risk factors for VTE were acute infection/and rheumatologic disorder (76.7%), reduced mobility (41.1%), having heart and /or respiratory failure (21.5%), elderly age ⩾70 years (13.7%), active cancer (10.5%), and acute myocardial infarction or ischemic stroke (12.8%).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, another study from Ethiopia reported that about 47.6% of medical inpatients had a significant DVT risk. 24 However, in our study, thromboprophylaxis was given to only 25.1% of patients and 6.84% of them received it without having risk or they were at lower risk which doesn’t mandate thromboprophylaxis and four patients were given pharmacologic prophylaxis despite the patients had absolute contraindication. There were 26 patients from high-risk group who did not get prophylaxis which may be due to ineligibility and/or contraindication, the fear of risk of bleeding and failure of prescribing them even for legible patients by prescribers.…”
Section: Discussionmentioning
confidence: 57%
“…Deep venous thrombosis (DVT) can be prevented through non-pharmacologic prophylaxis (compression stockings, leg elevation, sequential compression devices (SCDs), ambulation, and vena cava filter) and pharmacologic intervention, which is through the use of blood-thinning medications[ 2 , 11 , 27 ]. The most common blood thinner prophylaxis in Ethiopia is unfractionated heparin (UFH) and warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…The most common blood thinner prophylaxis in Ethiopia is unfractionated heparin (UFH) and warfarin. The major side effect of blood-thinning medications is an increased risk of bleeding and some patients are contraindicated for blood-thinning medications since they have a greater risk of developing adverse events[ 11 , 24 ]. The overall mortality rate in untreated patients is 30%, with approximately 10% of patients dying within 1 h of the event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation